Rethinking the relationship between international, EU and national law consent-based monism - Kirchmair, Lando 1986- (ASIL studies in international legal theory, 2024)
The interdisciplinary embedding and novel conceptual approach offered in the book to address the relationship between legal orders offers a significant and original contribution to the literature. The first part of the book provides a critical account of dominant approaches to explain this relationship where theories of Kelsenian monism, dualism, legal pluralism and constitutionalism are criticized. In the second part, Kirchmair engages with an innovative idea by applying insights from social contract theory to the relationship between international, EU and Member State law and establishes his theoretical approach: Consent-Based Monism. The book focuses on the most important structural characteristics of the external relations law of the EU as well as the primacy of EU law in lieu of national constitutional identity which is demonstrated in part three